Development of the MARPEX App Embedding the Mobile Augmented Reality Factors for Learning Motivation in Science Experiments - Gopalan, Valarmathie; Abu Bakar, Juliana Aida; Zulkifli, Abdul Nasir (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Mobile Augmented Reality (MAR) has grown exponentially over the last four decades from imagination to real physical experience, especially in education. Previously, experts have completed the concepts of effectiveness, usability, acceptance and understanding in designing MAR applications to introduce and expose technological advances. However, most of these applications are addressed extensively for classroom science learning, while science experiments receive little attention. Students have to go through difficulties in understanding the phenomena of science and consequently become dissatisfied with their grasp on basic knowledge and eventually cannot pursue higher education or career related to science. This paper presents the development of Mobile Augmented Reality for Physics (MARPEX) application for high school students. The purpose of this application is to enhance the learning motivation in science experiments through the content of modern science. It aims to provide an individual learning experience for each student in science experiments. The MARPEX app design has gone through several phases of filtering and evaluation based on the specified objectives. This application needs to maintain the factors necessary to achieve this goal. This app has been designed and developed specifically for science (physics) experiments on the topic of electromagnetism. The application encrypts several experimental instances with the addition of good visualization to understand this phenomenon and has real-life experimental experience.